Data and code for "Efficient calculation of the lattice thermal conductivity by atomistic simulations with ab-initio accuracy" - Brorsson, Joakim; Hashemi, Arsalan; Fan, Zheyong; Fransson, Erik; Eriksson, Fredrik; Ala-Nissila, Tapio; Krasheninnikov, Arkady V.; Komsa, Hannu-Pekka; Erhart, Paul (Chalmers University of Technology, 2021)
This data set contains data and code related to the publication "Efficient calculation of the lattice thermal conductivity by atomistic simulations with ab-initio accuracy".

The updated record contains force constant potential (FCP) files that are readable by hiphive 1.X The old versions require a version
Keywords: Force constant expansions; Force constant potentials; Molecular Dynamics Simulation; Physical Sciences; Fysik